Efektivitas Program Jaminan Persalinan Di Kabupaten Situbondo - Rupi'ah, Siti (Syntax Idea, 2021)
That most of the Insurance Recipients did not take care of the document requirements by themselves, they preferred to ask for help from another people who were considered to have more experience, such as village officials. Some people complained that The SOP wa too long and that there was no transfer of Authority if the officials responsible for the signing of recommendation is not in place. Gradual socialization has been carried out by Health Office, from the District to Village levels. The aim of this research is to analysis the effectiveness of Maternity Insurance Program in Situbondo. Data collection was carried out by interview, observation and documentation as well as the search of secondary data. The key informants were 3 people consisting of Health Office Head of Situbondo Regency, Head Division of Health Resources as Team Leader of Jampersal Program management and Jampersal verifier. There were also additional informants such as sub-district head, head of Community Health Center (PUSKESMAS), midwife of Puskesmas, village officials who take care of Jampersal, 3 pregnant women representing western, central and eastern regions which became the target of Jampersal beneficiaries. Descriptive Analysis was carried out through data collective analysis, condensation data, display data and verification data. The results showed that the Maternity Insurance Program in Situbondo was running effectively despite complains from people regarding bureaucranic structure and resources.